Sensorless Wavefront Correction in Two-Photon Microscopy Across Different Turbidity Scales - Sohmen, Maximilian; May, Molly A.; Barré, Nicolas; Ritsch-Marte, Monika; Jesacher, Alexander (Frontiers in Physics, 2022)
Adaptive optics (AO) is a powerful tool to increase the imaging depth of multiphoton scanning microscopes. For highly scattering tissues, sensorless wavefront correction techniques exhibit robust performance and present a straight-forward implementation of AO. However, for many applications such as live-tissue imaging, the speed of aberration correction remains a critical bottleneck. Dynamic Adaptive Scattering compensation Holography (DASH) – a fast-converging sensorless AO technique introduced recently for scatter compensation in nonlinear scanning microscopy – addresses this issue. DASH has been targeted at highly turbid media, but to-date it has remained an open question how it performs for mild turbidity, where limitations imposed by phase-only wavefront shaping are expected to impede its convergence. In this work, we study the performance of DASH across different turbidity regimes, in simulation as well as experiments. We further provide a direct comparison between DASH and a novel, modified version of the Continuous Sequential Algorithm (CSA) which we call Amplified CSA (a-CSA).